HRI London 2019: 10 Years of Excellence in Homeopathy Research - Roberts, E. Rachel; Mosley, Angelina J.; Tournier, Alexander L. (Homeopathy, 2020)
The Homeopathy Research Institute's (HRI's) 4th International Research Conference took place in the heart of London from 14 to 16 June 2019. With 352 attendees from 38 countries, this was HRI's largest and most international conference to date. HRI London 2019 will be remembered for the highest quality scientific programme so far, combined with a vibrant, positive atmosphere throughout, making it the perfect way to celebrate HRI's 10th Anniversary. Here we summarise the science presented during the intense 2.5-day programme.
Keywords: homeopathy research; systematic review; conference; HRI; clinical trials; fundamental research